Alimony and its proportional distribution in response to the obligation for several family units - Beltrán Torres, Fabricio Jahir (2025)
The rights of children and adolescents, as well as other beneficiaries entitled to support, are a priority that must be asserted. The objective is to determine the impact on the principle of the best interests of the child of the lack of legal regulations that enable the timely and proportional payment of child support by obligated payers with multiple households. The approach is mixed, descriptive-analytical, and statistical information was collected from the Ecuadorian Automatic Judicial Processing System (SATJE) and the Single System of Child Support (SUPA). The SUPA results reveal pensions below $200, and 22% of the cards are for pensions under $100. This demonstrates a clear inequality in the distribution of resources and compromises the best interests of the child. In conclusion, the application of proportional support in Ecuador presents deficiencies in its implementation, as effective mechanisms have not been established to guarantee an equitable distribution of resources for a payer with multiple beneficiaries.